ANALISA WACANA KRITIS PEMBERITAAN PEREMPUAN DALAM KASUS KORUPSI DI DETIK.COM - Widarini, Dwi Ajeng; Setyowati, Desy (Universitas Prof. Dr. Moestopo (Beragama), 2014)
Recently corruption and women amid a debate in Indonesia, since several names involved to corruption cases in Indonesia. Media also intensively reported corruption cases involving women. But unfortunately, elections raised angle was often not based on the main theme of corruption, but rather from their feminine side. In fact, the chosen diction tends to expose a side of sexuality with a description of the physical appearance. This research aims to determine how the women featured in the news on Detik.com. As one of the popular news site in Indonesia, Detik.com has a hits calculation system and page views to determine the amount of potential readers. The method used in this research is qualitative, descriptive. Using critical paradigm, and model of Sara Millss critical discourse analysis, focuses on two main aspects is subject-object position and readers position. Based on the results of this research, women are often raised in the news based on the stereotypes attached to her. Moreover, high ratings for coverage about women shows that our society are more interested in things that are sensational.